Flavonoids modify root growth and modulate expression of SHORT-ROOT and HD-ZIP III - Franco, Danilo Miralha [UNESP]; Silva, Eder Marques; Saldanha, Luiz Leonardo [UNESP]; Adachi, Sérgio Akira [UNESP]; Schley, Thayssa Rabelo [UNESP]; Rodrigues, Tatiane Maria [UNESP]; Dokkedal, Anne Ligia [UNESP]; Nogueira, Fabio Tebaldi Silveira; Rolim de Almeida, Luiz Fernando [UNESP] (Elsevier B. V., 2015)
Flavonoids are a class of distinct compounds produced by plant secondary metabolism that inhibit or promote plant development and have a relationship with auxin transport. We showed that, in terms of root development, Copaifera langsdorffii leaf extracts has an inhibitory effect on most flavonoid components compared with the application of exogenous flavonoids (glycosides and aglycones). These compounds alter the pattern of expression of the SHORT-ROOT and HD-ZIP III transcription factor gene family and cause morpho-physiological alterations in sorghum roots. In addition, to examine the flavonoid auxin interaction in stress, we correlated the responses with the effects of exogenous application of auxin and an auxin transport inhibitor. The results show that exogenous flavonoids inhibit primary root growth and increase the development of lateral roots. Exogenous flavonoids also change the pattern of expression of specific genes associated with root tissue differentiation. These findings indicate that flavonoid glycosides can influence the polar transport of auxin, leading to stress responses that depend on auxin.
Keywords: Allelopathic stress; Differential gene expression; Kaempferol-3-o-alpha-rhamnoside; Quercetin-3-o-alpha-rhamnoside; Root development